2008
DOI: 10.1007/s10765-008-0529-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of AlN–Ethanol Nanofluids

Abstract: Aluminum nitride (AlN) particles of 20 nm diameter were dispersed into ethanol by a two-step process, first magnetic striation and then ultrasonic agitation. Castor oil was added as a dispersant to improve the stability of the AlN suspension. The thermal conductivities of AlN-ethanol nanofluids were measured by a hot-disk method from 0.5 vol% to 4.0 vol% at temperatures of 273.15 K and 297.15 K. Results show about 20 % increase in the thermal conductivity of ethanol with the addition of 4.0 vol% at 273.15 K, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…For EG and PG based nanofluids with 4.0 vol% of AlN nanoparticles, the thermal conductivity increment ratios are about 16.5%, somewhat smaller than the ethanol based AlN nanofluid (Hu et al, 2008), apparently due to the larger diameter of AlN nanoparticle in our paper of 50 nm as compared to 20 nm of Hu et al (2008) which was much accompanied by aggregation (Prasher et al, 2006). Moreover, the ratios of thermal conductivity increment for nanofluids are related to the thermal conductivities of base fluids.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…For EG and PG based nanofluids with 4.0 vol% of AlN nanoparticles, the thermal conductivity increment ratios are about 16.5%, somewhat smaller than the ethanol based AlN nanofluid (Hu et al, 2008), apparently due to the larger diameter of AlN nanoparticle in our paper of 50 nm as compared to 20 nm of Hu et al (2008) which was much accompanied by aggregation (Prasher et al, 2006). Moreover, the ratios of thermal conductivity increment for nanofluids are related to the thermal conductivities of base fluids.…”
Section: Resultsmentioning
confidence: 50%
“…Nanofluids containing AlN nanoparticles have likewise the potential for heat transfer fluids with high thermal conductivity. To our knowledge, only one paper has been found reporting on the thermal transport properties of nanofluids containing AlN nanoparticles (Hu, Shan, Yu, & Chen, 2008), without, however mentioning the viscosities of nanofluids containing AlN nanoparticles. In the present work, the thermophysical properties of ethylene glycol (EG) and propylene glycol (PG) based AlN nanofluids were measured, including the effects of particle volume fraction, temperature, thermal conductivities of the base fluids, as well as the rheological properties of the nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…But not only, for example SiC [31e33] and AlN [34,35] nanoparticles are also commonly used for the preparation of the nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that thermal conductivity of the liquid increases when the nanoparticles are dispersed therein [8][9][10][11][12][13][14][15][16][17]. This increase might be particularly interesting both for engineers planning to practical applications of nanofluids is one of the most important factor for the values of thermal conductivity of nanofluids.…”
Section: Introductionmentioning
confidence: 99%